Cellulitis due to molluscum contagiosum. - Milano, A. (European Journal of Pediatric Dermatology, 2016)
Molluscum contagiosum is a self-healing viral infection of the child. The disease is caused by a DNA pox virus. Its prevalence in the population aged 0 to 16 years ranges between 5.1 and 11.5% (4). However, judging by the fact that the infection disappears spontaneously, does not recur and is exceptional in adults, it is likely that the percentage of children who pass the infection is much higher. Molluscum contagiosum can be associated with different types of inflammation, among which one that affects the individual elements and heralds self-healing, another following the use of caustic agents such as potassium hydroxide (3), a hypersensitivity eczematous dermatitis and finally a dermatitis reminiscent of Gianotti-Crosti syndrome (1). An infectious cellulitis due to molluscum contagiosum has been described in patients with AIDS (2, 4), but not in immunocompetent subjects as in our case.